Gambaran Tingkat Kecemasan pada Ibu Postpartum Spontan di Puskesmas Ibrahim Adjie Kota Bandung - Ishmah, Nuur Afifah; Pramatirta, A Yogi; Gumilang, Lani; Estiningtyas, Qorinah; Martini, Neneng (NUCLEUS, 2023)
The postpartum period is a critical time and predisposes women to experience anxiety, as they undergo a role transition into motherhood. If anxiety is left unaddressed, it can lead to postpartum depression and negatively impact cognitive, behavioral, and neurophysiological outcomes for the child. The purpose of this research is to assess the levels of anxiety among spontaneous postpartum mothers at the Ibrahim Adji Community Health Center in Bandung city. This study employs a descriptive method with a cross-sectional research design, involving a sample of 36 spontaneous postpartum mothers. The instrument used is the Postpartum Specific Anxiety Scale (PSAS). The research findings indicate that the majority of postpartum mothers experience mild anxiety at 41.6%, moderate anxiety at 25%, severe anxiety at 16.7%, and 16.7% of postpartum mothers have no anxiety. The conclusion of this study suggests that postpartum mothers tend to experience mild anxiety. It is hoped that healthcare professionals, especially midwives, can provide counseling and psychological support as these are crucial aspects during the postpartum period.